2022
DOI: 10.1155/2022/6950335
|View full text |Cite
|
Sign up to set email alerts
|

Damage Mechanism and Wave Attenuation Induced by Blasting in Jointed Rock

Abstract: This work uses a combination of simulations performed via numerical models and field observations studied the attenuation of deep-hole blasting stress waves and the evolution mechanism of cracks in a jointed rock mass. First, we conclude that the larger the joint angle is, the larger is the transmission coefficient and smaller is the fractal dimension. Second, the time difference between the peak stress difference and the maximum principal stress on both sides of the blasting hole in the horizontal direction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…σ u = σ td (11) where σ e is the Mises effective stress, σ u is the ultimate stress of the material, and σ td is the dynamic tensile strength of the rock, which is 59.5 MPa in this paper. (Note: The Mises effective stress mentioned above is the same concept as the effective stress described below.)…”
Section: Effective Stress Of Rock Mass On the Connection Of Two Blast...mentioning
confidence: 99%
See 1 more Smart Citation
“…σ u = σ td (11) where σ e is the Mises effective stress, σ u is the ultimate stress of the material, and σ td is the dynamic tensile strength of the rock, which is 59.5 MPa in this paper. (Note: The Mises effective stress mentioned above is the same concept as the effective stress described below.)…”
Section: Effective Stress Of Rock Mass On the Connection Of Two Blast...mentioning
confidence: 99%
“…As a result, scientists both at home and abroad have done extensive studies on the propagation of explosion stress waves in jointed rock masses. Fan and Song et al [11,12] studied the attenuation rules of explosive stress waves in single-jointed rock masses by combining numerical simulation and field tests and found that with an increase in the joint inclination angle, the attenuation of explosive stress waves increased and the amplitude of stress waves decreased. Li et al [13] studied the effect of different joint numbers on the attenuation of explosive stress waves through model tests and deduced the propagation equation of stress waves at multiple nonlinear joints.…”
Section: Introductionmentioning
confidence: 99%